Professional learning communities and job satisfaction in Icelandic preschools - Björnsdóttir, Sveinbjörg; Sigurðardóttir, Sigríður Margrét; Jóhannesdóttir, Anna Margrét (Tímarit um uppeldi og menntun, 2021)
The aim of the study was to shed light on the situation of a professional learning community within Icelandic preschools and its connection with the educational position and job satisfaction of staff, other than formal leaders.Numerous attempts have been made to capture the practices and characteristics of professional learning communities in educational settings (Hall & Hord, 2015; Huffman & Hipp, 2003; Stoll & Louis, 2007). In Iceland those efforts have mainly been aimed at the compulsory level (Anna Kristín Sigurðardóttir, 2010; Berglind Gísladóttir et al., 2019) but only rarely at the preschool level (Svava Björg Mörk & Rúnar Sigþórsson, 2011). However, the ideology of a professional learning community is prominent in the National Curriculum Guide for Preschools in Iceland (Mennta- og menningarmálaráðuneytið [Ministry of Education and Culture], 2011).In this study a professional learning communities’ assessment questionnaire developed by Huffman and Hipp (2003) and later revised (Hipp and Huffman, 2010; Olivier and Hipp, 2010) (Professional Learning Community Assessment - PLCA) is adapted to the Icelandic preschool work-situation and used to assess the perception of preschool staff (other than formal leaders); preschool teachers, staff with other pedagogical education and staff without any pedagogical education relating to professional learning communities. The assessment tool consists of five dimensions of professional learning communities: shared and supportive leadership; shared values and vision; collective learning and its application; shared personal practices; and supportive conditions, divided into relationships and structures (Olivier and Hipp, 2010).Data was obtained by a survey. Within one municipality, seven preschools were contacted that identified themselves as working within the ideology of professional learning communities. Principals of five schools accepted participation on behalf of their staff and provided their e-mail addresses. A questionnaire was sent to the staff, ...